The Heart (qalb) - Seyyed Hossein Nasr; Oludamini Ogunnaike (St Andrews Encyclopaedia of Theology)
In the Islamic tradition, the heart is the centre of the human being. Much more than just the physical organ that circulates blood throughout the body, the heart is central to the physical, emotional, intellective, ethical, and spiritual life of Muslims. The Qur’an and Hadith have provided a rich, nuanced vocabulary and description of the various dimensions of the human heart, and over the centuries, various Islamic disciplines and literatures have built upon this foundation to develop profound understandings of the heart as the meeting place of the ethical and intellectual, the Divine and the human, the eternal and temporal, the spiritual and the physical. Taken as a whole, the Islamic tradition presents itself as a ‘cure’ for hearts that are ‘diseased’, ‘hardened’, and ‘blind’, characterized by turbulence, ignorance, and selfishness, transforming them into ‘sound’ hearts characterized by limpidity, knowledge, tenderness, and receptivity to Divine theophanies. Within the Sufi tradition, this transformation is also described as a journey from the periphery of one’s being to its centre, into the heart itself, which a Prophetic tradition describes as ‘the throne of the All-Merciful’. Thus, the heart is at once the vehicle as well as the goal of the journey of human life; in the words of another saying of the Prophet of Islam, the heart contains the Divine Presence that is both our origin and final end.